Analisis Tingkat Kesehatan Bank Jatim dengan Menggunakan Metode RGEC Periode 2022-2023 Sebagai Dasar Pengambilan Keputusan - Siwi, Ghea Nada Ramadhani Putri; Sodik, Sodik; Fatoni, Irfan (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2025)
The purpose of this study is to determine the health level of Bank Jatim using the RGEC method as a basis for decision-making. The type of research used in this study is descriptive with a quantitative approach. Secondary data in this study is the published Annual Financial Report of Bank Jatim for the 2022-2023 period. The data analysis method used is financial statement analysis using the RGEC method. Where the Risk Profile is measured using the NPL and LDR indicators, GCG is measured using the Self-Assessment indicator, Earnings are measured using the ROA, ROE, NIM and BOPO indicators, Capital is measured using the CAR indicator. The results show that Bank Jatim's NPL in 2022 is in the "Healthy" category. Then in 2023 it is also in the "Healthy" category. Bank Jatim's LDR in 2022 is in the "Very Healthy" category. Then in 2023 it is also in the "Very Healthy" category. Bank Jatim's SA composite value in 2022 is in the "Fairly Good" category. Bank Jatim's SA composite score for 2023 was in the "Good" category. Bank Jatim's ROA for 2022 was in the "Healthy" category. It was also in the "Healthy" category in 2023. Bank Jatim's ROE for 2022 was in the "Very Healthy" category. It was also in the "Healthy" category in 2023. Bank Jatim's NIM for 2022 was in the "Very Healthy" category. It was also in the "Very Healthy" category in 2023. Bank Jatim's BOPO for 2022 was in the "Very Healthy" category. It was also in the "Very Healthy" category in 2023. Bank Jatim's CAR for 2022 was in the "Very Healthy" category. It was also in the "Very Healthy" category in 2023. Overall, Bank Jatim's Composite Rating 1 (PK-1) for 2022-2023 reflects Bank Jatim's overall "very healthy" condition.